Expression analysis of transforming growth factor beta (TGF-β) in oral squamous cell carcinoma - Arun Ganesh; P.P. Ashikha Shirin Usman; Ameya K.P.; Priya Thomas; Dhanraj M. Ganapathy; Durairaj Sekar (Oral Oncology Reports)
Objective: The most widely seen cancer in the neck and head portion is oral squamous cell carcinoma (OSCC), which is reported in more than 45 % of cases in some countries. Although much progress has been made to control OSCC in recent years, therapies for OSCC remain challenging. Interestingly, transforming growth factor β (TGF-β) plays an important role in the extracellular microenvironment and different cellular processes like migration, proliferation, etc. Thus, the goal of this research is to analyse the levels of TGF-β in OSCC patients and their adjacent normal tissue. Methods: 20 samples were collected from OSCC patients and adjacent normal tissue from Oral and Maxillofacial Surgery Department, Saveetha Dental College. The collected samples were subjected to staining studies. The RNA was isolated, and expression studies were done using the qRT-PCR method. The expression levels of genes in both normal and cancer tissues are analysed. Mean ± standard deviation data were shown in the study. Correlation study also done for systematic data. Results: Histological observation findings showed that moderately differentiated squamous cell carcinoma to be of higher frequency than well differentiated. Findings show that, when compared to normal tissue, OSCC samples had significantly increased TGF-β expression levels. Conclusion: From this study, TGF-β was found to be an important oncogene in tumor growth, and inhibition of TGF-β can be postulated as a potential treatment against OSCC.